Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2196/25494
|View full text |Cite
|
Sign up to set email alerts
|

Using Smartwatches to Observe Changes in Activity During Recovery From Critical Illness Following COVID-19 Critical Care Admission: 1-Year, Multicenter Observational Study

Abstract: Background As a sequela of the COVID-19 pandemic, a large cohort of critical illness survivors have had to recover in the context of ongoing societal restrictions. Objective We aimed to use smartwatches (Fitbit Charge 3; Fitbit LLC) to assess changes in the step counts and heart rates of critical care survivors following hospital admission with COVID-19, use these devices within a remote multidisciplinary team (MDT) setting to support patient recovery, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Despite the fact that the control group did not engage in any formal structured rehabilitation, the materials (including handouts, devices, and an app with a health diary) that were provided to the control group and the regular check-ins with the study team may help to explain the similar between-group results [ 7 ]. In the Hunter et al [ 1 ] study on the recovery of COVID-19 survivors, participants indicated that smartwatches motivated them to recover and increase their physical activity levels. This is important, as the use of smartwatches is a relatively low-cost, low-burden, and easily implementable posthospital intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the fact that the control group did not engage in any formal structured rehabilitation, the materials (including handouts, devices, and an app with a health diary) that were provided to the control group and the regular check-ins with the study team may help to explain the similar between-group results [ 7 ]. In the Hunter et al [ 1 ] study on the recovery of COVID-19 survivors, participants indicated that smartwatches motivated them to recover and increase their physical activity levels. This is important, as the use of smartwatches is a relatively low-cost, low-burden, and easily implementable posthospital intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is among the first to report objective physical activity data (step counts) from COVID-19 survivors. In the only other study that we are aware of, Hunter et al [ 1 ] found that individuals who were recovering from COVID-19 and were admitted to a critical care unit had an average of 4359 (SD 3488) steps per day in the first month after discharge and increased their step counts to an average of 7914 (SD 4146) steps per day at 1 year ( P =.003) [ 1 ]. In our study, participants had a similar median baseline step count of 4928 (IQR 3083-7574) at 1 week after study enrollment (mean 3.5 weeks after hospital discharge), which is below the targets for healthy adults (around 8000-10,000 daily steps) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We explicitly see potential for use in interventional studies, as it is a great tool to evaluate interventions that, for instance, focus on promoting out-of-home mobility, fostering new routines, changing mobility habits, or following patients after cardiac rehabilitation. As an individualized/tailored approach is used often (compare [33,34]), we believe it is possible to develop our system even further and add live feedback options for the user. Overall, GPS-based measurements can add great value to various study designs and populations and should be considered and examined more often in health research.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%